Recent Advances in Stimuli-Sensitive Amphiphilic Polymer-Paclitaxel Prodrugs - Zhou, Man; Wen, Lijuan; Wang, Cui; Lei, Qiao; Li, Yongxiu; Yi, Xiaoqing (Frontiers in Bioengineering and Biotechnology, 2022)
Paclitaxel (PTX) is a broad-spectrum chemotherapy drug employed to treat a variety of tumors. Nevertheless, due to its poor water solubility, the clinical application of PTX is limited. Adjuvants are widely used in the clinic to overcome the poor solubility of PTX. However, these adjuvants not only have side effects, but also have poor pharmacokinetics and biodistribution. The smart drug delivery systems provides another promising strategy to improve the solubility, permeability and stability of drugs, and further promote sustained and controlled release, thereby increasing the therapeutic efficacy and reducing side effect. In the construction of drug delivery systems, polymeric prodrugs show great advantages due to their high drug loading and stability. A number of the groundbreaking work in the field of PTX-based stimulus-sensitive polymeric prodrug micelles are summarized in this paper. And dividing them into four main parts according to the type of stimulus (pH, reduction, enzyme and reactive oxygen species (ROS)). The design, synthesis and biomedical applications of stimulus-responsive polymeric prodrugs of PTX is reviewed. And briefly discussed the research results and prospects of this field.